Mediated truth - Bruno Strulovici (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2017)
Many facts are learned through the intermediation of individuals with special access to information, such as law enforcement officers, employees with a security clearance, or experts with specific knowledge. This paper considers whether societies can learn about such facts when information is costly to acquire, cheap to manipulate, and produced sequentially. The answer is negative under an "asymptotic scarcity" condition pertaining to the amount of evidence available which distinguishes, for example, between reproducible scientific evidence and the evidence generated by a crime.
Keywords: 330